Development of early predictors of cerebral ischaemia after subarachnoid haemorrhage - Garry, P (2015)
Aneurysmal subarachnoid haemorrhage (SAH) is a severe disease often leading to profound disability and death. There has been increasing interest in nitric oxide (NO) signalling after brain injury, as it appears to influence many of the cellular metabolic pathways that eventually result in apoptosis and neuronal dysfunction. Many animal studies have shown exogenous cerebral NO donation appears to confer neuroprotective effects. It has shown to particularly affect many of the pathophysiological processes that occur after SAH. The work presented here describes two studies. The first study correlates changes in quantitative electroencephalography (qEEG) with the infusion of a cerebral NO donor, sodium nitrite after severe (World Federation of Neurosurgeon’s grades 3, 4 and 5) SAH. There is a need for better cerebral function assessment tools in this patient cohort as the usefulness of neurological examination is limited. The second study investigates magnetic resonance imaging (MRI) methods of evaluating acute tissue blood flow changes that occur after severe SAH, namely vessel encoded pseudo-continuous arterial spin labelling (VEPCASL). The results from the first study demonstrate that qEEG changes in response to an NO donor correlate with the subsequent development of delayed cerebral ischaemia (DCI) and poor clinical outcomes. The results from the second study show that VEPCASL can be used to obtain measures of regional cerebral blood flow changes that occur over time in the acute stages of severe SAH. This thesis demonstrates that bedside EEG monitoring is an extremely useful tool to give additional information regarding neuronal health after severe SAH. We have offered a new insight into the mechanisms behind therapeutic repletion of NO, aiding its development as a potential new therapy. We have also shown that VEPCASL MRI is a useful tool in assessing cerebral perfusion in the acute stages of injury.